On multiplicative (generalized)-(α,β)-derivations in prime rings - Garg, Chirag; Sharma, R. K. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 512.5 We discuss some algebraic identities related to multiplicative (generalized)-derivations and multiplicative (generalized)-(α,β)-derivations on appropriate subsets in prime rings.